Natalia Ginzburg fra la scoperta della vocazione teatrale e l’esigenza di descrivere la problematicità del quotidiano e dell’intimismo domestico: l’esempio di Ti ho sposato per allegria (ACME, 2023)
The purpose of this study is to shed some light on Ginzburg’s dramaturgical work to place it within the Italian dramaturgy, trying to understand how her debut in the theater takes place. The first dramaturgical work of the writer I married you for joy is examined, which gives rise to such an intense activity as a theatrical author, which covers the period from 1965 to 1991. The study shows that the theater for Ginzburg is the continuation of the narrative vein with other means and the possibility of giving voice to different points of view. It also tries to explain why Ginzburg’s theater is defined as ‘Word Theatre’ or ‘Theatre Chat’ and why the use of scene headings in her plays is limited. At the end of the essay we can understand that Ginzburg’s theater is a chronicle theater that tends to process the present in a domestic key.